DIVERSIFICATION OF FERMENTED MILK PRODUCT: KEFIR AND YOGHURT - Imam Thohari; Tri Eko Susilorini; Anie Eka Kusumastuti; Firman Jaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
This IbIKK is one of the entrepreneurship activities in the Laboratory of Processing of Animal Product Technology Faculty of Animal Husbandry Brawijaya University. The objective of this activity was to produce fermented milk products, such as yogurt ice candy, yogurt drink, kefir drink, kefir mask and kefir toner that was free of preservatives and has been done research and ready to sell to various consumer: direct consumers, through cooperatives in campus environment and through electronic media. The production of Probiotics was conducted in Processing Technology Laboratory using batch pasteurizer, and incubator to produce quality yoghurt and kefir. The fermented milk products were packed in packs: yogurt ice candy (40 mL) yogurt drink (125 mL), kefir drink (125 mL), kefir mask (100 g) and kefir (100 mL) toner at consumer prices compared to brands other. The marketing method was conducted by direct promotion in Brawijaya University (students, staffs and lecturers), through partnership of Malang university cooperative, through stall around student's residence, canteens in elementary, junior and senior high school in Malang and through the website, www.natural-probiotic.co.id and through social networking.